Implementation of Decision Support System for Scholarship Recipients at Bank Indonesia - Dian Megah Sari; Nurhikma Arifin; Nurfitrianingsih; Andi M Yusuf (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2022)
The Bank Indonesia Scholarship is a Bank Indonesia social program in the form of tuition assistance for undergraduate students (S1) at various State Universities (PTN). However, often in terms of determining scholarship recipients it is not right on target, this is caused because the scholarship award has not used the tools or methods used to determine scholarship recipients, for that a system is designed to determine scholarship recipients. The selection process for Bank Indonesia Scholarships requires accuracy and a long time because each student data will be compared one by one according to predetermined criteria and is also prone to accidental human errors. Meanwhile, Bank Indonesia has not determined a method to help select prospective scholarship recipients and the selection process is still carried out manually by comparing the student data of prospective scholarship recipients one by one, for this reason, the application of the algorithm in this study is to combine the Fuzzy Multiple Decision Making (FMAM) method and Simple Additive Weighting (Saw) with provisions and criteria that have been determined by Bank Indonesia. The FMADM method is used to find alternatives from a number of alternatives with predetermined criteria and the SAW method is used to rank the existing alternatives. The results of this study are used as a tool in making decisions to recommend scholarship recipients.